THE SAFETY AND OUTCOME OF ACUTE ISCHAEMIC STROKE PATIENTS WITH COVID-19 TREATED WITH INTRAVENOUS RECOMBINANT TISSUE PLASMINOGEN ACTIVATOR: A SYSTEMATIC REVIEW - Machin, Abdulloh; Setjaputra, Vina Lidya; Susianto, Steven Christian; Husni, Nadya; Sugondo, Alexander Tikara (MNJ (Malang Neurology Journal), 2024)
Background: Strokes associated with SARS-CoV-2 may be linked to increased mortality rates. The utilization of intravenous thrombolysis is anticipated to enhance the clinical results in such patients. Moreover, emerging evidence underscores the importance of evaluating the safety and effectiveness of intravenous thrombolysis in individuals suffering from Acute Ischaemic Stroke along with COVID-19. Objective: To assess the safety and effectiveness of intravenous thrombolysis in Acute Ischaemic Stroke patients with COVID-19. Methods: A systematic literature search (Pubmed, Elsevier, and Cochrane database) with keywords (((intravenous thrombolysis) AND (acute ischemic stroke)) AND (covid-19)) AND (outcome))). We selected research studies for evaluation based on specific inclusion and eligibility criteria. Two independent reviewers then proceeded to extract and analyze various data points, including the name of the first author, the year of publication, the study's design, the National Institute of Health Stroke Scale (NIHSS) scores at admission and post-treatment, hospitalization-related mortality, and the occurrence of hemorrhagic transformation. Results: Three studies (n=153 patients) were included, mostly men with advanced age with the most common comorbidity being hypertension. Median of NIHSS Score of subjects on admission is 11, 12, and 13, with interquartile range from 3 to 20 (minor to severe stroke). The mRS at discharge and 1 month after admission is: 0–2 pts in 57 patients, ≥2 in 43 patient. Hemorrhagic transformation involved 3.23% of patients from total samples, death within hospitalization and 1-month mortality were in 23 patients (15%). In numerous studies, there was inadequate data available to determine the precise reason for mortality. Conclusion: Following IV-rTPA therapy, our COVID-19 infection subjects' mRS scores ranged from mild to moderate disability. Fifteen percents of all subjects died, and 3.23% of subjects experienced hemorrhagic transformation. However, majority of our subjects have high median NIHSS scores at admission, advanced age, complicated with baseline risk factors as high blood pressure, diabetes, and hyperlipidemia.